Editorial: Methodology, Context and Quality - Heila Lotz Sisitka (Environmental Association of Southern Africa, 2013)
Note: This edition of the Southern African Journal of Environmental Education (SAJEE) is a 'double volume' and contains papers submitted in 2012 and 2013. The production of a double volume has been necessitated by administrative problems experienced by the journal production team in 2012, which affected the successful publication of a 2012 edition. However, the Council of the Environmental Education Association of Southern Africa (EEASA) agreed to respond by producing a double-volume edition for 2012/2013. Journal readers are reminded that the production of this journal is voluntary and depends heavily on voluntary administration and other systems. The patience of authors and readers in the 2012/2013 years of production is much appreciated. The 2012/2013 double-volume SAJEE is richly textured with two think pieces that open the journal, thirteen research papers and three viewpoint papers. The papers in the 2012/2013 double volume include papers by authors from Sweden, the United Kingdom, India, South Africa, Zimbabwe, Botswana, Zambia, Lesotho, Ethiopia, Mozambique and Kenya, showing that the journal is attracting not only southern African authorship, but also authorship from across the continent and internationally. The present edition of the journal is also interesting in that three different perspectives stand out, namely methodology, context and quality, perspectives which permeate the journal papers in various ways.